Are Short Sellers Informed? Evidence from the Bond Market - Kecskés, Ambrus; Mansi, Sattar A.; Zhang, Andrew (Jianzhong (The Accounting Review, 2013)
ABSTRACT We examine whether short sellers in the equity market provide valuable information to investors in the bond market. Using a sample of publicly traded bond data covering the period from 1988 to 2011, we find that firms with high short interest have lower credit ratings and are more likely to have their ratings downgraded. We also find that firms with highly shorted stocks are associated with higher bond yield spreads (about 24 basis points). Evidence of causality from short interest spikes and a natural experiment based on the SEC's Regulation SHO pilot program confirms our findings. Overall, our results suggest that equity short sellers provide predictive information to creditors in the bond market. JEL Classifications: G12; G14. Data Availability: Data are publicly available from the sources identified in the study with the exception of the bond data from Lehman Brothers, which is a proprietary dataset.